The skeleton in the Smithsonian - Roy, Ron, 1940- (Roy, Ron, 1940- Capital mysteries, 2003)
When Leonard Fisher claims to be the long-lost heir to the Smithsonian fortune, KC and Marshall set out to prove that he is a phony.